2020
DOI: 10.1136/bmjopen-2019-034965
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a traditional Chinese mind–body exercise, Baduanjin, on the physical and cognitive functions in the community of older adults with cognitive frailty: study protocol for a randomised controlled trial

Abstract: IntroductionCognitive frailty (CF) is a clinical manifestation characterised by the simultaneous presence of both physical frailty and cognitive impairment among older adults without dementia and has become a new target for healthy ageing. Increasing evidence shows that regular Baduanjin (a traditional Chinese mind–body exercise) training is beneficial in improving physical function and cognitive ability in the older adults. The primary aim of this trial is to observe the effect of Baduanjin on physical and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 36 publications
0
28
0
Order By: Relevance
“…62 Of note, a randomized controlled trial is currently being planned to investigate the effects of a traditional Chinese mind-body exercise, Baduanjin, on cognitive and physical function in older adults with cognitive frailty. 102 As noted above, cognitive frailty is multifactorial, and multimodal interventions including promoting physical activity, exercise, a healthy diet, smoking cessation, active social participation, avoidance of polypharmacy, and oral care and metabolic control may represent preventive measures for cognitive frailty. 103 A 6month multi-domain intervention trial is being planned to address the cognitive, physical, nutritional and psychosocial domains of cognitive frailty in older adults.…”
Section: Interventions For Cognitive Frailtymentioning
confidence: 99%
“…62 Of note, a randomized controlled trial is currently being planned to investigate the effects of a traditional Chinese mind-body exercise, Baduanjin, on cognitive and physical function in older adults with cognitive frailty. 102 As noted above, cognitive frailty is multifactorial, and multimodal interventions including promoting physical activity, exercise, a healthy diet, smoking cessation, active social participation, avoidance of polypharmacy, and oral care and metabolic control may represent preventive measures for cognitive frailty. 103 A 6month multi-domain intervention trial is being planned to address the cognitive, physical, nutritional and psychosocial domains of cognitive frailty in older adults.…”
Section: Interventions For Cognitive Frailtymentioning
confidence: 99%
“…The third popular topic is the biomarkers of physical and cognitive function among older people, such as testosterone de ciency [39]. Moreover, researchers had paid much attention on the preventive interventions / programs for cognitive frailty including resistance exercise training [40], mHealth brisk walking intervention [41], Baduanjin [42], and multi-domain interventions [43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…At present, only some studies with low level of evidence have confirmed the positive effect of Baduanjin exercise on balance function and fall prevention in middle-aged and elderly people. [ 34 36 ]…”
Section: Discussionmentioning
confidence: 99%